CREDIT FOR MSMES, PRIVATE CREDIT, AND REGIONAL ECONOMIC GROWTH IN INDONESIA: A PANEL VECTOR AUTOREGRESSIVE ANALYSIS - Kristianto, Doddy (Polytechnic of State Finance STAN, 2019)
This study aims to analyse the dynamic between credit to micro, small, and medium enterprises (MSMEs), private credit, and regional economic growth in Indonesia. A panel vector autoregression model is employed to understand the dynamic in the model. Unlike previous cross-country studies, this paper is using provincial panel data. The relationship between variables in the model are connected under the same regulation, monetary authority, and fiscal institution. Thus, there will be no effects that appear from the differences of institutions. The results suggest that the interaction between credit to MSMEs and private credit is bi-directional. Also, credit to MSMEs and private credit does affect regional economic growth. However, the result does not provide strong evidence for causality from regional economic growth to credit for MSMEs or private credit.Â Penelitian ini bertujuan untuk menganalisis hubungan dinamis antara kredit kepada UMKM, kredit kepada sektor privat, dan pertumbuhan ekonomi regional di Indonesia. Untuk memahami hubungan ketiga variable tersebut, penelitian ini menggunakan panel vector autoregression (Panel VAR). Penelitian ini berbeda dengan penelitian antar negara yang telah ada sebelumnya karena penelitian ini menggunakan data pada level provinsi. Data pada level provinsi memiliki keunggulan karena berada pada sistem regulasi perbankan dan regulasi fiskal yang sama sehingga tidak terdapat efek dari adanya perbedaan institusional. Dari penelitian ini diketahui bahwa interaksi antara kredit kepada UMKM dan kredit kepada sektor privat adalah dua arah. Kredit kepada UMKM dan kredit kepada sektor privat mempengaruhi pertumbuhan ekonomi regional, namun tidak terdapat bukti kuat yang menjelaskan hubungan sebaliknya.